Rallying Around Empty Signifiers: understanding and Defining Anti-Government Protest in the Netherlands - Frens, Isabelle (Perspectives on terrorism, 2023)
As in many other parts of Europe, anti-government protest has been a topic of political and academic discussion in the Netherlands for some years. The definition of what anti-government protest entails and which groups and individuals it refers to is not as straightforward as it may seem. Where other institutions have attempted to place anti-governmental protest movements in frameworks of traditional extremist movements, the Dutch authorities describe the anti-government protestors as a group that is characterised by its pluriformity and fluidity. In 2022, they have even changed the term ‘anti-governmental’ to ‘anti-institutional’ to more broadly refer to the set of targets that the movement opposes, which includes government, but also the media, the scientific community, experts and the judicial system. In this paper we try to understand the anti-government, or anti-institutional, protest in the Netherlands using a different lens. We use Ernesto Laclau’s discourse theory and its concept of empty signifiers to show how opposed interests and goals can be seen as a unified ideology to its proponents. Instead of trying to primarily define the group of people who are anti-government by their actions or characteristics, we look at how those actors define themselves and how they see their struggle against the authorities. We describe the rise and dynamics of anti-government protest in the Netherlands since the start of the COVID-19 pandemic, focusing on "genealogies" and the eclectic topics of the protest movement. We compare our observations with the definition of anti-governmental protest and the anti-institutional narrative as used by the authorities. We arrive at the conclusion that analysing the anti-government protest through the lens of their shared ideas and grievances gives us more insight into the nature and dynamics of this movement than solely looking through the lens of the potential threat to the democratic legal order.